Human evolution - Narasimhan, Vagheesh (Henry Stewart Talks, 2022)
Human evolution from the fossil record, Early hominid lineages in and out of Africa, The genomic revolution, The advent of ancient DNA, Archaic admixture, Sedimentary DNA, Paleoproteomics, Natural selection in humans in the past and present